Adverse childhood experiences and early life inflammation in the Avon longitudinal study of parents and children. (December 2020) - Lacey, Rebecca E; Bartley, Mel; Kelly-Irving, Michelle; Bevilacqua, Leonardo; Iob, Eleonora; Kelly, Yvonne; Howe, Laura D
Highlights: There is a reliance on ACE scores and single adversity approaches in ACEs research. We compare ACE scores, individual ACEs and latent class analysis (LCA) for early life inflammation. LCA identified four clusters. 'Maternal mental health problems' was associated with lower CRP for girls. IL-6 was higher for parental divorce and lower for emotional abuse, paternal mental health problems, parental offending and alcohol misuse. Associations between paternal mental health problems and emotional abuse with lower IL-6 were only seen for boys. Abstract: Background: Adverse childhood experiences (ACEs) have been associated with poorer health across the life course. Previous studies have used cumulative risk scores (ACE scores) or individual ACEs but these two approaches have important shortcomings. ACE scores assume that each adversity is equally important for the outcome of interest and the single adversity approach assumes that ACEs do not co-occur. Latent class analysis (LCA) is an alternative approach to operationalising ACEs data, identifying groups of people co-reporting similar ACEs. Here we apply these three approaches for ACEs operationalisation with inflammation in childhood with the aim of identifying particular ACEs or ACE combinations that are particularly associated with higher inflammation in early life. Methods: Using data from the Avon Longitudinal Study of Parents and Children (ALSPAC) we compare ACE scores, single adversities and LCA-derived ACE clusters in their relationships with Interleukin-6 at age 9 (n = 4935) and C-Reactive Protein (CRP) at age 9 (n = 4887). ACEs included were parental separation/divorce, parental alcohol problems, parental mental health problems, parental offending, inter-parental violence, parental drug misuse, and physical, emotional and sexual abuse. Results: Two thirds of the sample reported at least one ACE. Mother's mental health problems was the most frequently reported ACE (32.3 %). LCA identified four ACE classes – 'Low ACEs' (81.1 %), 'Maternal mental health problems' (10.3 %), 'Maternal mental health problems and physical abuse' (6.3 %) and 'Parental conflict, mental health problems and emotional abuse' (2.4 %). Parental separation/divorce was associated with higher IL-6. Parental alcohol problems, paternal mental health problems, parental convictions and emotional abuse were associated with lower levels of IL-6. Associations for paternal mental health problems and emotional abuse were only observed for boys. ACE score and LCA-derived ACE classes were not associated with differences in IL-6. Girls in the 'Maternal mental health problems' cluster had lower CRP levels. Conclusions: Specific adversities and adversity combinations are important for differences in childhood inflammation. Some associations were only observed for girls or boys.